Ceftolozane-Tazobactam for the Treatment of Multidrug-Resistant Pseudomonas aeruginosa Infections: A Multicenter Study. (31st October 2018) - Gallagher, Jason C; Satlin, Michael J; Elabor, Abdulrahman; Saraiya, Nidhi; McCreary, Erin K; Molnar, Esther; El-Beyrouty, Claudine; Jones, Bruce M; Dixit, Deepali; Heil, Emily L; Claeys, Kimberly C; Hiles, Jon; et al.
Abstract: Background: Multidrug-resistant Pseudomonas aeruginosa infections remain common in hospitals worldwide. We investigated the outcomes associated with the use of ceftolozane-tazobactam for the treatment of these infections. Methods: Data were collected retrospectively from 20 hospitals across the United States about adults who received ceftolozane-tazobactam for the treatment of multidrug-resistant P aeruginosa infections of any source for at least 24 hours. The primary outcome was a composite of 30-day and inpatient mortality, and secondary outcomes were clinical success and microbiological cure. Multivariable regression analysis was conducted to determine factors associated with outcomes. Results: Two-hundred five patients were included in the study. Severe illness and high degrees of comorbidity were common, with median Acute Physiology and Chronic Health Evaluation (APACHE) II scores of 19 (interquartile range [IQR], 11–24) and median Charlson Comorbidity Indexes of 4 (IQR, 3–6). Delayed initiation of ceftolozane-tazobactam was common with therapy started a median of 9 days after culture collection. Fifty-nine percent of patients had pneumonia. On susceptibility testing, 125 of 139 (89.9%) isolates were susceptible to ceftolozane-tazobactam. Mortality occurred in 39 patients (19%); clinical success and microbiological cure were 151 (73.7%) and 145 (70.7%), respectively. On multivariable regression analysis, starting ceftolozane-tazobactam within 4 days of culture collection was associated with survival (adjusted odds ratio [OR], 5.55; 95% confidence interval [CI], 2.14–14.40), clinical success (adjusted OR, 2.93; 95% CI, 1.40–6.10), and microbiological cure (adjusted OR, 2.59; 95% CI, 1.24–5.38). Conclusions: Ceftolozane-tazobactam appeared to be effective in the treatment of multidrug-resistant P aeruginosa infections, particularly when initiated early after the onset of infection.